2022
DOI: 10.1097/qai.0000000000002949
|View full text |Cite
|
Sign up to set email alerts
|

Similar But Different: Integrated Phylogenetic Analysis of Austrian and Swiss HIV-1 Sequences Reveal Differences in Transmission Patterns of the Local HIV-1 Epidemics

Abstract: a,b the Swiss HIV Cohort Study and the Austrian HIV Cohort StudyObjectives: Phylogenetic analyses of 2 or more countries allow to detect differences in transmission dynamics of local HIV-1 epidemics beyond differences in demographic characteristics.Methods: A maximum-likelihood phylogenetic tree was built using pol-sequences of the Swiss HIV Cohort Study (SHCS) and the Austrian HIV Cohort Study (AHIVCOS), with international background sequences. Three types of phylogenetic cherries (clusters of size 2) were an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Furthermore, our study findings indicate that the HIV-1 B subtype is prevalent among both female and heterosexual male participants. Similarly, phylogenetic analyses conducted in the Czech Republic (30), Slovenia (31), and Austria (32), showed that the HIV-1 B subtype remains the predominant form, although other HIV subtypes such as A, C, and F, as well as recombinant circulating forms CRF01_AE and CRF02_AG, CRF02_AB are seen to be less frequent. Moreover, unique recombinant forms (URFs) were infrequently detected in Slovenia by obtaining near full-length genome sequences and performing detailed recombination analysis (33).…”
Section: Phylogenetic Analysismentioning
confidence: 94%
“…Furthermore, our study findings indicate that the HIV-1 B subtype is prevalent among both female and heterosexual male participants. Similarly, phylogenetic analyses conducted in the Czech Republic (30), Slovenia (31), and Austria (32), showed that the HIV-1 B subtype remains the predominant form, although other HIV subtypes such as A, C, and F, as well as recombinant circulating forms CRF01_AE and CRF02_AG, CRF02_AB are seen to be less frequent. Moreover, unique recombinant forms (URFs) were infrequently detected in Slovenia by obtaining near full-length genome sequences and performing detailed recombination analysis (33).…”
Section: Phylogenetic Analysismentioning
confidence: 94%